Improving Opinion Summarization by Assessing Sentence Importance in On-line Reviews - Anchiêta, Rafael T.; Sousa, Rogério F. de; Moura, Raimundo S.; Pardo, Thiago A. S. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2017: Anais do XI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2017)
This paper describes an approach for improving a state of the art opinion summarization method, incorporating the assessment of sentence importance in on-line reviews. We compare the enriched method to its original version and show that we significantly outperform it, producing more informative summaries.